Electromagnetic shielding nanofiber composite membrane with high strength and magnetoelectric synergism and preparation method thereof

By using PVA-co-PE nanofibers and UHMWPE composite films combined with RGO and Fe3O4, the problem of poor mechanical properties of existing electromagnetic shielding materials is solved, and high strength and excellent electromagnetic shielding performance are achieved.

CN119507257AActive Publication Date: 2025-02-25WUHAN TEXTILE UNIV
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411401414.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-09
Publication Date
2025-02-25
Estimated Expiration
2044-10-09

AI Technical Summary

Technical Problem

Due to the high permeability threshold, existing conductive polymer composites require high fill content and large thickness to achieve ideal conductivity and EMI shielding properties, but this results in reduced flexibility, mechanical properties and processability of the material, reducing its usefulness.

Method used

PVA-co-PE nanofibers and ultra-high molecular weight polyethylene fibers (UHMWPE) are used as base materials, and combined with reduced graphene oxide (RGO) and magnetic iron tetroxide nanoparticles (Fe3O4) as dielectric loss medium and magnetic loss medium, nanofiber composite membranes with high strength and magnetoelectric synergistic effects are prepared by high-speed shear, vacuum-assisted suction filtration and ultraviolet radiation crosslinking.

Benefits of technology

The nanofiber composite film that efficiently absorbs and reflects electromagnetic waves has excellent mechanical properties and electromagnetic shielding performance. It shows efficient electromagnetic shielding performance in the X-band, Ku-band and K-band, improving the practicality of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119507257A_ABST
    Figure CN119507257A_ABST
Patent Text Reader

Abstract

The invention provides an electromagnetic shielding nanofiber composite membrane with high strength and magnetoelectric synergy and a preparation method thereof, and belongs to the field of electromagnetic shielding materials. According to the preparation method, PVA-co-PE nanofibers and ultra-high molecular weight polyethylene fibers are used as base material raw materials, reduced graphene oxide is used as a dielectric loss medium, and magnetic ferroferric oxide nanoparticles are used as a magnetic loss medium; the PVA-co-PE / UHMWPE / RGO / Fe3O4 nanofiber composite membrane with high strength and toughness and magnetoelectric synergistic effect, which is used for efficiently absorbing and reflecting electromagnetic waves, is prepared by the methods of high-speed shearing of PVA-co-PE nanofiber, vacuum-assisted suction filtration, ultraviolet radiation crosslinking and the like. On one hand, UHMWPE and PVA-co-PE are introduced for cross-linking to construct an internal composite enhanced cross-linked structure, and the mechanical property of the composite membrane is greatly improved; on the other hand, the RGO and the magnetic Fe3O4 nano-particles interact to form a layered alternate distribution structure of the RGO and the magnetic Fe3O4 nano-particles, and the prepared composite film has excellent electromagnetic shielding performance in the ultra-wideband range of the X wave band, the Ku wave band and the K wave band.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of electromagnetic shielding materials, and in particular to an electromagnetic shielding nanofiber composite film with high strength and magneto-electric synergy and a preparation method thereof. Background Art

[0002] Electromagnetic interference shielding materials can effectively reduce electromagnetic radiation pollution to the human body and electronic devices by absorbing or reflecting electromagnetic waves. In the prior art, conductive polymer composites (CPCs) contain different conductive nanofillers. The added conductive nanofillers have a high specific surface area, which can form an interface between the polymer and the nanomaterial that is conducive to the polarization loss of electromagnetic waves, and can greatly improve the electromagnetic wave absorption efficiency. Such as metal nanowires, reduced graphene oxide (rGO), multi-walled carbon nanotubes (MWCNTs) and two-dimensional transition metal carbides / nitrides (2D MXene), have been developed to supplement or replace traditional hard and high-density metal shielding materials.

[0003] However, due to the high permeation threshold of CPCs, high filler content and large thickness are usually required to obtain ideal conductivity and EMI shielding performance, but this will lead to reduced flexibility, mechanical properties (especially strength and toughness) and processability of the material, reducing its practicality.

[0004] In view of this, it is necessary to design an electromagnetic shielding nanofiber composite membrane with high strength and magneto-electric synergy and a preparation method thereof to solve the above problems. Summary of the invention

[0005] In view of the technical problems existing in the background technology, the present application provides an electromagnetic shielding nanofiber composite membrane with high strength and magneto-electric synergy and a preparation method thereof. The preparation method uses PVA-co-PE nanofibers and ultra-high molecular weight polyethylene fibers (UHMWPE) as base materials, reduced graphene oxide (RGO) dispersion as dielectric loss medium, and magnetic ferroferric oxide nanoparticle (Fe3O4) dispersion as magnetic loss medium. By high-speed shearing of PVA-co-PE nanofibers, vacuum-assisted filtration, and ultraviolet radiation cross-linking, a high-strength and toughness magneto-electric synergistic PVA-co-PE / UHMWPE / RGO / Fe3O4 nanofiber composite membrane for efficient absorption and reflection of electromagnetic waves is prepared.

[0006] In a first aspect, the present invention provides a method for preparing an electromagnetic shielding nanofiber composite film with high strength and magneto-electric synergy, comprising the following steps:

[0007] S1, preparing a PVA-co-PE nanofiber suspension having a fiber content of 0.5 wt% to 2 wt%;

[0008] S2, mixing the PVA-co-PE nanofiber suspension prepared in step S1 with a reduced graphene oxide dispersion and a magnetic ferroferric oxide nanoparticle dispersion to form a PVA-co-PE / RGO / Fe3O4 mixed suspension; wherein the mass ratio of the components in the PVA-co-PE / RGO / Fe3O4 mixed suspension is PVA-co-PE:RGO:Fe3O4=1.5:(0.05-0.07):(0.07-0.09);

[0009] S3, adding ultra-high molecular weight polyethylene fibers to the PVA-co-PE / RGO / Fe3O4 mixed suspension to obtain a multi-component mixed suspension; wherein the mass of the ultra-high molecular weight polyethylene fibers is 2wt% to 7wt% of the mass of the PVA-co-PE nanofibers;

[0010] S4, placing the multi-component mixed suspension obtained in step S3 in a vacuum-assisted filtration device, and obtaining a PVA-co-PE and UHMWPE nanofiber composite membrane by vacuum-assisted filtration;

[0011] S5, immersing the PVA-co-PE and UHMWPE nanofiber composite membrane obtained in step S4 in a crosslinking agent, placing it under ultraviolet light for crosslinking, and naturally air-drying to obtain an electromagnetic shielding nanofiber composite membrane with high strength and magnetoelectric synergy.

[0012] In the technical solution of the embodiment of the present application, ultra-high molecular weight polyethylene fiber (UHMWPE) is introduced, PVA-co-PE nanofiber and ultra-high molecular weight polyethylene fiber (UHMWPE) are used as base material raw materials, reduced graphene oxide (RGO) dispersion is used as dielectric loss medium, magnetic ferroferric oxide nanoparticle (Fe3O4) dispersion is used as magnetic loss medium, UHMWPE and PVA-co-PE are cross-linked by adding a cross-linking agent and then cross-linking by ultraviolet radiation to construct an internal composite reinforced cross-linked structure, which greatly enhances the mechanical properties of the composite film and solves the problem of poor mechanical properties of conventional electromagnetic shielding film materials.

[0013] Furthermore, in step S3, in the multi-component mixed suspension, the mass percentage of the PVA-co-PE nanofibers is 0.5wt% to 2wt%, the mass percentage of the reduced graphene oxide is 0.05wt% to 0.07wt%, the mass percentage of the magnetic ferrosoferric oxide nanoparticles is 0.07wt% to 0.09wt%, and the mass percentage of the ultra-high molecular weight polyethylene fibers is 0.01wt% to 0.14wt%.

[0014] Furthermore, in step S5, the mass percentage concentration of the crosslinking agent is 3% to 5%, the crosslinking time under ultraviolet light is 20 to 40 minutes, and the intensity is 50 μW / cm 2 .

[0015] Furthermore, the specific strength of the ultra-high molecular weight polyethylene fiber is 20 to 40 MPa·cm 3 / g, specific modulus is 85~125GPa·cm 3 The ultra-high molecular weight polyethylene fiber has a diameter of 10 μm to 20 μm and a length of 30 to 50 μm.

[0016] Furthermore, in step S1, the PVA-co-PE nanofiber suspension is prepared by dispersing isopropanol, deionized water and PVA-co-PE nanofibers in a volume ratio of 1:1 in a certain proportion under a high-speed shearing machine.

[0017] Furthermore, the diameter of the PVA-co-PE nanofiber is 200nm to 800nm, and the length is 20 to 50μm.

[0018] Furthermore, in step S5, the cross-linking agent is obtained by diluting trimethylolpropane trimethacrylate with ethanol.

[0019] In the second aspect, the embodiment of the present application provides an electromagnetic shielding nanofiber composite membrane with high strength and magneto-electric synergy, which is prepared by the aforementioned technical solution. The nanofiber composite membrane is a porous network structure, and the electromagnetic shielding performance in the X-band is 35 to 37 dB, the electromagnetic shielding performance in the Ku-band is 33 to 36 dB, and the K-band EMI SE value is 35 to 38 dB.

[0020] The technical solution of the embodiment of the present application uses a reduced graphene oxide (RGO) dispersion as a dielectric loss medium and a magnetic ferroferric oxide nanoparticle (Fe3O4) dispersion as a magnetic loss medium, and obtains a high-strength and high electromagnetic shielding performance nanofiber composite membrane through the multi-stage synergistic effect of chemical crosslinking and multi-component interface enhancement (electrostatic interaction and weak chemical bonds between the interface of magnetic Fe3O4 nanoparticles and RGO, and chemical crosslinking between the interface of PVA-co-PE nanofibers and ultra-high molecular weight polyethylene fibers).

[0021] Furthermore, the RGO in the nanofiber composite membrane is a sheet-like structure, and the magnetic Fe3O4 nanoparticles are deposited on the surface of the RGO, and the two present an overall layered alternating distribution structure in the nanofiber composite membrane.

[0022] Furthermore, the fracture stress of the nanofiber composite membrane is 10-12 MPa.

[0023] RGO interacts with magnetic ferroferric oxide nanoparticles through electrostatic interaction and weak chemical bonds. There are many free electrons on the surface of RGO that interact with the electrons of magnetic ferroferric oxide nanoparticles to form an alternating structure of reduced graphene oxide (RGO) and magnetic ferroferric oxide nanoparticles (Fe3O4). Specifically, RGO is a sheet structure, and magnetic Fe3O4 nanoparticles are deposited on the surface of RGO. The nanofiber composite membrane presents an overall layered alternating distribution structure, which significantly improves the conductivity and electromagnetic interference shielding performance. The prepared nanofiber composite membrane has excellent electromagnetic shielding performance in the ultra-wide frequency range of X-band, Ku-band, and K-band, providing a new strategy for further broadening the application field of electromagnetic shielding materials.

[0024] The above description is only an overview of the technical solution of the present application. In order to more clearly understand the technical means of the present application, it can be implemented in accordance with the contents of the specification. In order to make the above and other purposes, features and advantages of the present application more obvious and easy to understand, the specific implementation methods of the present application are listed below. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] In order to more clearly illustrate the technical solution of the present application, the following is a brief introduction to the drawings used in the present application. Obviously, the drawings described below are only some embodiments of the present application, and for ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.

[0026] Figure 1 The present invention is a schematic flow chart of a method for preparing an electromagnetic shielding nanofiber composite membrane with high strength and magneto-electric synergy.

[0027] Figure 2 This is a microscopic electron microscope image of a region of the electromagnetic shielding nanofiber composite membrane with high strength and magneto-electric synergy prepared in Example 1.

[0028] Figure 3 This is a microscopic electron microscope image of another area of ​​the electromagnetic shielding nanofiber composite membrane with high strength and magneto-electric synergy prepared in Example 1.

[0029] Figure 4 This is a graph showing the electromagnetic shielding performance test results of the fiber membranes prepared in Example 1 and Comparative Example 1.

[0030] Figure 5 This is a graph showing the mechanical properties test results of the fiber membranes prepared in Example 1 and Comparative Example 1. DETAILED DESCRIPTION

[0031] The following embodiments of the technical solution of the present application will be described in detail in conjunction with the accompanying drawings. The following embodiments are only used to more clearly illustrate the technical solution of the present application, and are therefore only used as examples, and cannot be used to limit the scope of protection of the present application.

[0032] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by technicians in the technical field to which this application belongs; the terms used herein are only for the purpose of describing specific embodiments and are not intended to limit this application; the terms "including" and "having" in the specification and claims of this application and the above-mentioned figure descriptions and any variations thereof are intended to cover non-exclusive inclusions.

[0033] In the description of the embodiments of the present application, the technical terms "first", "second", etc. are only used to distinguish different objects, and cannot be understood as indicating or implying relative importance or implicitly indicating the number, specific order or primary and secondary relationship of the indicated technical features. In the description of the embodiments of the present application, the meaning of "multiple" is more than two, unless otherwise clearly and specifically defined.

[0034] Reference to "embodiments" herein means that a particular feature, structure, or characteristic described in conjunction with the embodiments may be included in at least one embodiment of the present application. The appearance of the phrase in various locations in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described herein may be combined with other embodiments.

[0035] In the description of the embodiments of the present application, the term "and / or" is only a description of the association relationship of the associated objects, indicating that there may be three relationships. For example, A and / or B can represent: A exists alone, A and B exist at the same time, and B exists alone. In addition, the character " / " in this article generally indicates that the associated objects before and after are in an "or" relationship.

[0036] In the description of the embodiments of the present application, the term "multiple" refers to more than two (including two). Similarly, "multiple groups" refers to more than two groups (including two groups), and "multiple pieces" refers to more than two pieces (including two pieces).

[0037] In the description of the embodiments of the present application, unless otherwise clearly specified and limited, technical terms such as "installed", "connected", "connected", "fixed" and the like should be understood in a broad sense. For example, it can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection or an electrical connection; it can be a direct connection or an indirect connection through an intermediate medium, and it can be the internal connection of two elements or the interaction relationship between two elements. For those of ordinary skill in the art, the specific meanings of the above terms in the embodiments of the present application can be understood according to the specific circumstances.

[0038] In a first aspect, the present invention provides a method for preparing an electromagnetic shielding nanofiber composite film with high strength and magneto-electric synergy, comprising the following steps:

[0039] S1, preparing a PVA-co-PE nanofiber suspension having a fiber content of 0.5 wt% to 2 wt%;

[0040] S2, mixing the PVA-co-PE nanofiber suspension prepared in step S1 with a reduced graphene oxide dispersion and a magnetic ferroferric oxide nanoparticle dispersion to form a PVA-co-PE / RGO / Fe3O4 mixed suspension; wherein the mass ratio of the components in the PVA-co-PE / RGO / Fe3O4 mixed suspension is PVA-co-PE:RGO:Fe3O4=1.5:(0.05-0.07):(0.07-0.09);

[0041] S3, adding ultra-high molecular weight polyethylene fibers to the PVA-co-PE / RGO / Fe3O4 mixed suspension to obtain a multi-component mixed suspension; wherein the mass of the ultra-high molecular weight polyethylene fibers is 2wt% to 7wt% of the mass of the PVA-co-PE nanofibers;

[0042] S4, placing the multi-component mixed suspension obtained in step S3 in a vacuum-assisted filtration device, and obtaining a PVA-co-PE and UHMWPE nanofiber composite membrane by vacuum-assisted filtration;

[0043] S5, immersing the PVA-co-PE and UHMWPE nanofiber composite membrane obtained in step S4 in a crosslinking agent, placing it under ultraviolet light for crosslinking, and naturally air-drying to obtain an electromagnetic shielding nanofiber composite membrane with high strength and magnetoelectric synergy.

[0044] This application introduces ultra-high molecular weight polyethylene fiber (UHMWPE), takes PVA-co-PE nanofiber and ultra-high molecular weight polyethylene fiber (UHMWPE) as base material raw materials, takes reduced graphene oxide (RGO) dispersion as dielectric loss medium, and magnetic ferroferric oxide nanoparticle (Fe3O4) dispersion as magnetic loss medium, and prepares high-strength and toughness magnetoelectric synergistic PVA-co-PE / UHMWPE / RGO / Fe3O4 nanofiber composite membrane for efficient absorption and reflection of electromagnetic waves by high-speed shearing of PVA-co-PE nanofiber, vacuum-assisted filtration and ultraviolet radiation cross-linking.

[0045] Electromagnetic interference shielding materials attenuate incident electromagnetic waves through a combination of electrical, magnetic and dielectric losses. Introducing magnetic particles into conductive polymer composites can promote absorption due to magnetic losses, thereby reducing the harm of secondary reflections of electromagnetic waves. Magnetic ferroferric oxide nanoparticles (Fe3O4) can effectively attenuate incident electromagnetic waves through magnetic losses due to their strong magnetic properties.

[0046] The high conductivity of reduced graphene oxide (RGO) helps to form an effective conductive path, which can form an interface between the polymer and the nanomaterial that is beneficial to the polarization loss capability of electromagnetic waves, making the composite material show good prospects in electromagnetic interference shielding capability.

[0047] RGO interacts with magnetic ferroferric oxide nanoparticles through electrostatic effects and weak chemical bonds. There are many free electrons on the surface of RGO that interact with the electrons of magnetic ferroferric oxide nanoparticles to form an alternating distribution structure of reduced graphene oxide (RGO) and magnetic ferroferric oxide nanoparticles (Fe3O4). Specifically, RGO is a sheet structure, and magnetic Fe3O4 nanoparticles are deposited on the surface of RGO, presenting an overall layered alternating distribution structure in the nanofiber composite membrane. The electrical conductivity and electromagnetic interference shielding performance are significantly improved, and the prepared nanofiber composite membrane has excellent electromagnetic shielding performance in the ultra-wide frequency range of X-band, Ku-band, and K-band, providing a new strategy for further broadening the application field of electromagnetic shielding materials.

[0048] The PVA-co-PE / UHMWPE / RGO / Fe3O4 nanofiber membrane prepared in this application has a porous network structure, high absorption performance and high strength and toughness. These excellent comprehensive properties have great potential for the application field of electromagnetic shielding materials.

[0049] In step S1, a PVA-co-PE nanofiber suspension is prepared by dispersing isopropyl alcohol, deionized water and PVA-co-PE nanofibers in a volume ratio of 1:1 in a certain proportion under a high-speed shearing machine.

[0050] The diameter of PVA-co-PE nanofibers is 200nm~800nm, and the length is 20~50μm.

[0051] Ultra-high molecular weight polyethylene fiber has high specific strength and high specific modulus. Specifically, the specific strength of ultra-high molecular weight polyethylene fiber is 20-40 MPa·cm 3 / g, specific modulus is 85~125GPa·cm 3 / g. The diameter of ultra-high molecular weight polyethylene fiber is 10μm to 20μm, and the length is 30 to 50μm.

[0052] In step S5, the mass percentage concentration of the crosslinking agent is 3% to 5%, the crosslinking time under ultraviolet light is 20 to 40 minutes, and the intensity is 50 μW / cm 2 .

[0053] This application introduces ultra-high molecular weight polyethylene fiber (UHMWPE). UHMWPE and PVA-co-PE are cross-linked by adding a cross-linking agent and then cross-linking by ultraviolet radiation to construct an internal composite reinforced cross-linking structure, thereby enhancing the mechanical properties of the composite film and solving the problem of poor mechanical properties of conventional electromagnetic shielding film materials.

[0054] Specifically, in step S3, in the multi-component mixed suspension, the mass percentage of PVA-co-PE nanofibers is 0.5wt% to 2wt%.

[0055] The mass percentage of reduced graphene oxide is 0.05wt% to 0.07wt%, the mass percentage of magnetic ferrosoferric oxide nanoparticles is 0.07wt% to 0.09wt%, and the mass percentage of ultra-high molecular weight polyethylene fibers is 0.01wt% to 0.14wt%.

[0056] In step S5, the cross-linking agent is obtained by diluting trimethylolpropane trimethacrylate with ethanol.

[0057] In the second aspect, the embodiment of the present application provides an electromagnetic shielding nanofiber composite membrane with high strength and magneto-electric synergy, which is prepared by the aforementioned preparation method. The prepared nanofiber composite membrane has a porous network structure, and its electromagnetic shielding performance in the X-band is 35 to 37 dB, the electromagnetic shielding performance in the Ku-band is 33 to 36 dB, and the K-band EMI SE value is 35 to 38 dB.

[0058] The RGO in the nanofiber composite membrane is a lamellar structure, and the magnetic Fe3O4 nanoparticles are deposited on the surface of RGO. The two present an overall layered alternating distribution structure in the nanofiber composite membrane.

[0059] The fracture stress of the nanofiber composite membrane is 10-12 MPa, showing good mechanical properties.

[0060] Some specific embodiments are listed below. It should be noted that the embodiments described below are exemplary and are only used to explain the present application, and should not be construed as limiting the present application. If specific techniques or conditions are not specified in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. The reagents or instruments used that do not specify the manufacturer are all conventional products that can be obtained commercially.

[0061] Example 1

[0062] See also Figure 1 As shown, this embodiment provides a method for preparing an electromagnetic shielding nanofiber composite membrane with high strength and magneto-electric synergy, comprising the following steps:

[0063] S1, preparing a PVA-co-PE nanofiber suspension with a fiber content of 2 wt%;

[0064] S2, mixing the PVA-co-PE nanofiber suspension prepared in step S1 with a reduced graphene oxide dispersion and a magnetic ferroferric oxide nanoparticle dispersion to form a PVA-co-PE / RGO / Fe3O4 mixed suspension; wherein the mass ratio of the components in the PVA-co-PE / RGO / Fe3O4 mixed suspension is PVA-co-PE:RGO:Fe3O4=1.5:0.06:0.08;

[0065] S3, adding ultra-high molecular weight polyethylene fibers to the PVA-co-PE / RGO / Fe3O4 mixed suspension to obtain a multi-component mixed suspension; wherein the mass of the ultra-high molecular weight polyethylene fibers is 5wt% of the mass of the PVA-co-PE nanofibers;

[0066] S4, placing the multi-component mixed suspension obtained in step S3 in a vacuum-assisted filtration device with a vacuum degree of -0.1 MPa, and obtaining a PVA-co-PE and UHMWPE nanofiber composite membrane by vacuum-assisted filtration;

[0067] S5, immersing the PVA-co-PE and UHMWPE nanofiber composite membrane obtained in step S4 in a TMPTMA crosslinking agent (mass percentage concentration is 5%), and then placing it under ultraviolet light for crosslinking, and the ultraviolet intensity is 50 μW / cm 2 The treatment time is 30 minutes. After the cross-linking is completed, the PVA-co-PE and UHMWPE nanofiber composite membrane is taken out and naturally air-dried to obtain a high-strength and toughness "magnetic-electric" synergistic PVA-co-PE and UHMWPE cross-linked PVA-co-PE / UHMWPE / RGO / Fe3O4 nanofiber composite membrane.

[0068] See also Figures 2 to 3 The figure shows an electron microscope image of the electromagnetic shielding nanofiber composite membrane with high strength and magneto-electric synergy prepared in Example 1. As can be seen from the figure, RGO is a sheet structure, and magnetic Fe3O4 nanoparticles are deposited on the surface of RGO, presenting a layered alternating distribution structure in the nanofiber composite membrane as a whole.

[0069] Comparative Example 1

[0070] Comparative Example 1 provides a method for preparing a nanofiber membrane. Compared with Example 1, the difference is that step S3 and step S5 are not performed, that is, only the PVA-co-PE nanofiber suspension of step S1 is used to obtain a nanofiber composite membrane (PVA-co-PE / RGO / Fe3O4) by vacuum-assisted filtration.

[0071] See also Figures 4 to 5 As shown, the electromagnetic shielding performance and mechanical property test results of the fiber membranes prepared in Example 1 and Comparative Example 1 are shown.

[0072] from Figure 4 It can be seen that the nanofiber composite membrane (PVA-co-PE / UHMWPE / RGO / Fe3O4) prepared in Example 1 has significantly improved electromagnetic shielding performance in the X-band and Ku-band compared with the unmodified PVA-co-PE nanofiber membrane in Comparative Example 1. Specifically, in the X-band, its electromagnetic shielding is improved from 3 dB to 37 dB, and the performance is improved by more than 12 times. Figure 4 In the Ku band, its electromagnetic shielding is improved from 2dB to 33dB, and the performance is improved by more than 16 times. Figure 4 As shown in (b) in .

[0073] The EMI SE value in the K band has increased from 3dB to 36dB, which is nearly 12 times higher than before. Figure 4 As shown in (c) in .

[0074] from Figure 5 It can be seen that compared with the unmodified nanofiber composite membrane (PVA-co-PE / RGO / Fe3O4) of Comparative Example 1, the fracture stress of the nanofiber composite membrane (PVA-co-PE / UHMWPE / RGO / Fe3O4) prepared in Example 1 is increased from 5 MPa to 11 MPa, an increase of 140%, and its fracture strain is increased by 100%, showing good mechanical properties.

[0075] Comparative Example 2

[0076] Comparative Example 2 provides a method for preparing a nanofiber membrane. Compared with Example 1, the difference is that in step S2, no reduced graphene oxide is added to obtain a nanofiber composite membrane (PVA-co-PE / UHMWPE / Fe3O4). The rest is roughly the same as Example 1 and will not be repeated here.

[0077] Comparative Example 3

[0078] Comparative Example 3 provides a method for preparing a nanofiber membrane. Compared with Example 1, the difference is that in step S2, no Fe3O4 is added to obtain a nanofiber composite membrane (PVA-co-PE / UHMWPE / RGO). The rest is roughly the same as Example 1 and will not be repeated here.

[0079] Comparative Example 4

[0080] Comparative Example 4 provides a method for preparing a nanofiber membrane. Compared with Example 1, the difference is that in step S2, the reduced graphene oxide is replaced by carbon nanotubes to obtain a nanofiber composite membrane (PVA-co-PE / MW-CNTs / Fe3O4). The rest is basically the same as Example 1 and will not be repeated here.

[0081] Comparative Example 5

[0082] Comparative Example 5 provides a method for preparing a nanofiber membrane. Compared with Example 1, the difference is that step S1 is not performed, and the multi-component mixed suspension does not contain PVA-co-PE nanofibers. The rest is roughly the same as Example 1 and will not be repeated here.

[0083] The electromagnetic shielding performance and mechanical properties of the nanofiber composite membranes prepared in Example 1 and Comparative Examples 1-5 were tested, and the results are shown in the following table.

[0084] Electromagnetic shielding (dB) Mechanical properties (MPa) Example 1 36 11 Comparative Example 1 36 5 Comparative Example 2 10 9 Comparative Example 3 19 10 Comparative Example 4 30 9 Comparative Example 5 / /

[0085] Experiments have shown that when PVA-co-PE nanofibers and ultra-high molecular weight polyethylene fibers (UHMWPE) are cross-linked by ultraviolet radiation, their electromagnetic shielding properties and mechanical properties are greatly improved.

[0086] In Example 1, the ultra-high molecular weight polyethylene fiber runs through the entire composite membrane structure, playing the role of a bridge and a support. In Comparative Example 1, the ultra-high molecular weight polyethylene fiber was not added, resulting in a decrease in mechanical properties. In Comparative Example 2, RGO was not added, and the composite membrane lacked a dielectric loss medium, resulting in a decrease in electromagnetic shielding performance. In Comparative Example 3, Fe3O4 was not added, and the composite membrane lacked a magnetic loss medium, resulting in a decrease in electromagnetic shielding performance.

[0087] Comparative Example 4 uses carbon nanotubes instead of reduced graphene oxide, but the effects on electromagnetic shielding and mechanical properties are not good. The reason may be that the carbon nanotubes cannot interact with the magnetic Fe3O4 nanoparticles through electrostatic effects and weak chemical bonds, and there are no free electrons on the surface of the carbon nanotubes that interact with the electrons of the magnetic Fe3O4 nanoparticles, which reduces the electromagnetic interference shielding performance of the nanofiber composite film.

[0088] In Comparative Example 5, the experiment found that without PVA-co-PE nanofibers, the main substrate was missing and the nanofiber membrane could not be formed.

[0089] Examples 2-3 and Comparative Examples 6-7

[0090] Examples 2-3 and Comparative Examples 6-7 provide a method for preparing an electromagnetic shielding nanofiber composite membrane with high strength and magneto-electric synergy, which is different from Example 1 in that the mass proportion of the ultra-high molecular weight polyethylene fiber in step S3 is changed, as shown in the following table. The rest is roughly the same as Example 1 and will not be repeated here.

[0091]

[0092] Experiments show that when the mass of UHMWPE accounts for a percentage of more than 7wt% of the mass of PVA-co-PE nanofibers, the interpenetration ratio of UHMWPE in the nanofiber composite membrane will be too high, and the toughness of the nanofiber composite membrane will be significantly reduced.

[0093] When the mass of UHMWPE accounts for less than 2wt% of the mass of PVA-co-PE nanofibers, the interpenetration ratio of UHMWPE in the nanofiber composite membrane will decrease, and the strength of the nanofiber composite membrane will decrease significantly.

[0094] Examples 4-6 and Comparative Examples 8-9

[0095] Examples 4-6 and Comparative Examples 8-9 provide a method for preparing an electromagnetic shielding nanofiber composite membrane with high strength and magnetoelectric synergy, which is different from Example 1 in that the mass ratio of each component in the PVA-co-PE / RGO / Fe3O4 mixed suspension in step S2 is changed, as shown in the following table. The rest is roughly the same as Example 1 and will not be repeated here.

[0096]

[0097] It can be seen from the above table that when the mass ratio of each component in the PVA-co-PE / RGO / Fe3O4 mixed suspension exceeds the range of 1.5:(0.05~0.07):(0.07~0.09), the electrostatic interaction and weak chemical bond force between RGO and magnetic Fe3O4 nanoparticles will be relatively weakened, and the electronic interaction between the free electrons on RGO and the magnetic Fe3O4 nanoparticles will also be relatively reduced, and the electromagnetic interference shielding performance will be weakened.

[0098] It should be noted that the present application is not limited to the above-mentioned embodiments. The above-mentioned embodiments are only examples, and the embodiments having the same structure as the technical idea and exerting the same effect within the scope of the technical solution of the present application are all included in the technical scope of the present application. In addition, without departing from the scope of the main purpose of the present application, various modifications that can be thought of by those skilled in the art to the embodiments and other methods of combining some of the constituent elements in the embodiments are also included in the scope of the present application.

Claims

1. A method for preparing an electromagnetic shielding nanofiber composite membrane with high strength and magneto-electric synergy, characterized in that: The following steps are involved: S1, preparing a PVA-co-PE nanofiber suspension having a fiber content of 0.5 wt% to 2 wt%; S2, mixing the PVA-co-PE nanofiber suspension prepared in step S1 with a reduced graphene oxide dispersion and a magnetic ferroferric oxide nanoparticle dispersion to form a PVA-co-PE / RGO / Fe3O4 mixed suspension; wherein the mass ratio of the components in the PVA-co-PE / RGO / Fe3O4 mixed suspension is PVA-co-PE:RGO:Fe3O4=1.5:(0.05-0.07):(0.07-0.09); S3, adding ultra-high molecular weight polyethylene fibers to the PVA-co-PE / RGO / Fe3O4 mixed suspension to obtain a multi-component mixed suspension; wherein the mass of the ultra-high molecular weight polyethylene fibers is 2wt% to 7wt% of the mass of the PVA-co-PE nanofibers; S4, placing the multi-component mixed suspension obtained in step S3 in a vacuum-assisted filtration device, and obtaining a PVA-co-PE and UHMWPE nanofiber composite membrane by vacuum-assisted filtration; S5, immersing the PVA-co-PE and UHMWPE nanofiber composite membrane obtained in step S4 in a crosslinking agent, placing it under ultraviolet light for crosslinking, and naturally air-drying to obtain an electromagnetic shielding nanofiber composite membrane with high strength and magnetoelectric synergy.

2. The method for preparing the electromagnetic shielding nanofiber composite membrane with high strength and magneto-electric synergy according to claim 1, characterized in that: In step S3, in the multi-component mixed suspension, the mass percentage of the PVA-co-PE nanofibers is 0.5wt% to 2wt%, the mass percentage of the reduced graphene oxide is 0.05wt% to 0.07wt%, the mass percentage of the magnetic ferrosoferric oxide nanoparticles is 0.07wt% to 0.09wt%, and the mass percentage of the ultra-high molecular weight polyethylene fibers is 0.01wt% to 0.14wt%.

3. The method for preparing the electromagnetic shielding nanofiber composite membrane with high strength and magneto-electric synergy according to claim 1, characterized in that: In step S5, the mass percentage concentration of the crosslinking agent is 3% to 5%, the crosslinking time under ultraviolet light is 20 to 40 minutes, and the intensity is 50 μW / cm 2 .

4. The method for preparing the electromagnetic shielding nanofiber composite membrane with high strength and magneto-electric synergy according to claim 1, characterized in that: The specific strength of the ultra-high molecular weight polyethylene fiber is 20-40 MPa·cm 3 / g, specific modulus is 85~125GPa·cm 3 / g; the diameter of the ultra-high molecular weight polyethylene fiber is 10μm to 20μm, and the length is 30 to 50μm.

5. The method for preparing the electromagnetic shielding nanofiber composite membrane with high strength and magneto-electric synergy according to claim 1, characterized in that: In step S1, the PVA-co-PE nanofiber suspension is prepared by dispersing isopropyl alcohol, deionized water and PVA-co-PE nanofibers in a volume ratio of 1:1 in proportion under a high-speed shearing machine.

6. The method for preparing the electromagnetic shielding nanofiber composite membrane with high strength and magneto-electric synergy according to claim 1, characterized in that: The diameter of the PVA-co-PE nanofiber is 200nm-800nm, and the length is 20-50μm.

7. The method for preparing the electromagnetic shielding nanofiber composite membrane with high strength and magneto-electric synergy according to claim 1, characterized in that: In step S5, the cross-linking agent is obtained by diluting trimethylolpropane trimethacrylate with ethanol.

8. An electromagnetic shielding nanofiber composite membrane with high strength and magneto-electric synergy, characterized in that: The nanofiber composite membrane is prepared by the preparation method described in any one of claims 1 to 7, and has a porous network structure, an electromagnetic shielding performance of 35 to 37 dB in the X-band, an electromagnetic shielding performance of 33 to 36 dB in the Ku-band, and an EMI SE value of 35 to 38 dB in the K-band.

9. The electromagnetic shielding nanofiber composite membrane with high strength and magneto-electric synergy according to claim 8, characterized in that: The RGO in the nanofiber composite membrane is a sheet-like structure, and the magnetic Fe3O4 nanoparticles are deposited on the surface of the RGO, and the two present an overall layered alternating distribution structure in the nanofiber composite membrane.

10. The electromagnetic shielding nanofiber composite membrane with high strength and magneto-electric synergy according to claim 8, characterized in that: The fracture stress of the nanofiber composite membrane is 10-12 MPa.

Citation Information

Patent Citations

  • Light and flexible graphene based multi-element compound wave absorbing film and preparation method thereof

    CN107840324A

  • Flexible graphene-based composite film, and preparation method and application thereof as electromagnetic shielding material

    CN108003364A

  • Electromagnetic interference shielding nano-composite film with asymmetric alternating multilayer structure and preparation method of electromagnetic interference shielding nano-composite film

    CN115103582A

  • Random number generator, integrated circuit having the same, and operating method thereof

    KR1020230067465A

  • Composition for preventing or treating recurrent liver cancer comprising GULP1 inhibitor

    KR1020240158798A